Morphometric Analysis of the Tibial Tunnel after Primary and Revision Anterior Cruciate Ligament Reconstruction - Veizi E; Cay N; Sezgin BS; Sahin A; Firat A; Bozkurt M (Malaysian Orthopaedic Journal)
Introduction: Anterior cruciate ligament (ACL) reconstruction is a commonly performed surgical procedure. The objectives of this retrospective comparative study are (1) to evaluate the obliquity, size and the intra-articular aperture shape of the tibial tunnel in patients operated with an anteromedial portal technique, and (2) to determine their possible relation with revision surgery. Materials and methods: Patients operated for a primary ACL reconstruction between 2014 and 2018 were eligible. All patients of primary and revision ACL fulfilling the inclusion criteria were assessed for presence of a knee CT scan within one month of surgery and at least three years of follow-up. Several radiological parameters were measured for the study, among which: Tunnel height, Coronal tunnel angle, Maximal tunnel width and Sagittal tunnel inclination. Multivariate analyses were performed to identify parameters correlated with revision. Results: Mean age of the primary group was 30.5±8.4 versus 29.4±8.0 of the revision group. The majority of patients were males in both groups (n=33, 76.7% and n=38, 95.0%, respectively). A longer diameter of the intra-articular ellipse (p=0.005) and an increased mid-tunnel to TT distance on the axial plane (p=0.006) were significantly correlated with revision. A ROC curve analysis determined a cut-off value of 27.9mm from the tubercle was an optimal entry point. Conclusion: A greater distance between the mid-point of the tibial tunnel entrance and the centre of the tibial tubercle is linked to a higher risk of revision. An elongated elliptic shape in the antero-posterior plane also correlates with revision risk.